2010
DOI: 10.1111/j.1750-3639.2010.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Disruption and Cajal Body Disassembly are Nuclear Hallmarks of DNA Damage‐Induced Neurodegeneration in Purkinje Cells

Abstract: The Purkinje cell (PC) degeneration (pcd) phenotype results from mutation in nna1 gene and is associated with the degeneration and death of PCs during the postnatal life. Although the pcd mutation is a model of the ataxic mouse, it shares clinical and pathological characteristics of inherited human spinocerebellar ataxias. PC degeneration in pcd mice provides a useful neuronal system to study nuclear mechanisms involved in DNA damage-dependent neurodegeneration, particularly the contribution of nucleoli and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 73 publications
4
70
0
Order By: Relevance
“…As PC degeneration progressed, an increase in the ␥H2AX-positive nuclear domains was observed by immunofluorescence, as reported previously (24). The signal of this histone mark colocalized with the H4K20me3-positive heterochromatin domains (Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As PC degeneration progressed, an increase in the ␥H2AX-positive nuclear domains was observed by immunofluorescence, as reported previously (24). The signal of this histone mark colocalized with the H4K20me3-positive heterochromatin domains (Fig.…”
Section: Resultssupporting
confidence: 86%
“…In a previous study (24), we have demonstrated that the pcd mutation causes disruption of the nucleolus in PCs, with transcriptional inhibition of ribosomal genes and consequently a deficit in the biogenesis of ribosomes. Our present results indicate that the pcd mutation also induces the repression of protein-coding genes in extensive domains of the genome of PCs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…76 A cellular hallmark of the disease is the progressive accumulation of DNA damage associated with a defective DNA repair, resulting in a severe inhibition of transcription of both ribosomal and protein-coding genes. 60 Gene silencing in Purkinje cells clearly correlates with progressive disruption of both nucleoli and CBs. 60 Interestingly, in addition to a severe loss of CBs, coilin was redistributed as a thin shell around the nucleolus (Fig.…”
Section: Cajal Bodies In Neuropathological Disordersmentioning
confidence: 99%
“…31,32 Several studies have shown that CB number correlates with neuronal size and global transcriptional activity. 31,57,59,60 For example, sensory ganglion neurons include 3 cell-size categories related to their different transcriptional and bioelectrical activities: small, medium and large neurons. In rats, the mean CB number increases from 1.1 per cell in small neurons, to 1.8 and 2.9 in medium and large neurons, respectively, indicating a close relationship between cell body size, a parameter directly related to global transcriptional and translational activity of the neuron, 61 and CB formation.…”
mentioning
confidence: 99%